Microbial Protein Synthesis by Cellulolytic Bacterial Isolates from Feces of Indonesian Endemic Herbivores - Pramartaa, Ikhsan Qodri; Wiryawan, Komang G.; Suharti, Sri (Universitas Djuanda, 2024)
Cellulolytic bacterial play an important role in the synthesis of microbial protein in the small intestine as high-quality protein. This research aimed to observe the growth patterns of cellulolytic bacterial isolates from the feces of endemic herbivorous animals in Indonesia, and to evaluate the effect of the addition of cellulolytic bacterial isolates on the synthesis of microbial proteins in vitro. The study used a completely randomized design with four treatments and five replications. The treatments included T0 = Concentrate mix 40%: elephant grass 30%: palm leaves 30% (control), T1 = T0 + 105 CFU mL-1 cellulolytic bacterial isolate, T2 = T0 + 106 CFU mL-1 cellulolytic bacterial isolate, and T3 = T0 + 107 CFU mL-1 cellulolytic bacterial isolate. Variables measured were the growth pattern of bacterial isolates, bacterial population at the optimal growth point, and microbial protein synthesis. The results showed growth pattern of cellulolytic bacterial isolates from Muntjac, Deer and Anoa feces have similar pattern, and was different from the growth pattern of bacterial isolates from bison feces. The optimal growth point of cellulolytic bacterial isolates from the feces of Muntjac, Deer, and Anoa at the 8th hour of incubation with bacterial populations of 1.3 x 109 CFU mL-1, 1.7 x 109 CFU mL-1, and 1.4 x 109 CFU mL-1. The growth pattern and optimal point of cellulolytic bacterial isolates from the feces of Bison at the 12th hour after incubation with bacterial populations of 1,1 x 1010 CFU mL-1. The addition of cellulolytic bacterial isolates did not affect microbial protein synthesis.